Changes of precipitation extremes in arid Central Asia. (29th April 2017) - Zhang, Man; Chen, Yaning; Shen, Yanjun; Li, Yupeng
Abstract: Despite growing evidence of increasing precipitation extremes around the world, research into extreme precipitation events in Central Asia (CA) is still scarce. In this study, based on daily precipitation records from 22 meteorological stations, several methods were used to detect the spatial-temporal distribution, abrupt change and return periods for six extreme precipitation indices as well as the total annual precipitation during 1938–2005 in CA. The results show that all precipitation indices experienced increasing trend except for annual maximum number of consecutive dry days (CDD), which had a significant decreasing trend. Abrupt changes for most of precipitation indices mainly occurred around 1957 during 1938–2005. Return periods for all seven precipitation indices concentrated in 10-year period. Meanwhile, all precipitation indices showed spatial diversity and heterogeneity, and the entire area tended to be wetter and experienced fewer dry conditions. Understanding these changes of precipitation extremes in CA will definitely benefit to water resource management, natural hazard prevention and mitigation, and reliable future projections in this region.